Challenges of Teaching to the New Generation of IT Students - Challiol, Cecilia (2019)
Today, due to the tremendous growth of the software industry, there are a wide variety of job opportunities for it students; in many countries, this motivates undergraduate students to begin working as developers before they have finished their computing education. Sometimes, this situa- tion causes students to take longer to finish their careers. In addition, this situation impacts the profile of students who participate in university courses since they might have real experience on the topics of the university curricula. Thus, teach- ing the new generation of it students has become challenging, not only to be motivational for them, but also to provide them with relevant knowledge beyond the intended syllabus.